Foraging Activity and Trophic Spectrum of Red Ant Pogonomyrmex barbatus Smith, 1858, in Productivity-Contrasted Microenvironments - Rafael Guzmán-Mendoza; Gabriela Castaño-Meneses; José Alejandro Zavala-Hurtado (Psyche: A Journal of Entomology)
Foraging strategies can be influenced by many factors such as abundance, availability, and toxicity of the resources. In arid zones, the distribution and productivity of plants also act as additional factors that affect foraging strategies. Twenty colonies of Pogonomyrmex barbatus ants were studied in an arid zone of central Mexico to evaluate the trophic niche breadth in two sites with contrasting productivities in terms of their diversity and amount of resources during two seasons. The results suggest that when the resources are abundant as in the rainy season, the trophic niche breadth is reduced in sites with high productivity and, in the same sites, the trophic niche breadth increases when the resources are limited as in the dry season. In contrast, the trophic niche breadth is similar in both conditions of resource availability (i.e., rainy and dry seasons) at sites with low productivity. During the dry season, populations of P. barbatus showed a similar foraging behavior in sites with high and low productivity. Thus, the particular characteristics of a site can significantly affect the foraging strategies of the ants in those environments.